Media Pembelajaran Berbasis Teknologi di MI/SD - Lingga Saniman Derajat; Rena Widayanti; Samsul Susilawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Learning at the MI/SD level requires learning processes and experiences that can help students understand the lessons they will study. Learning media has an important role as an intermediary between teachers and students to understand the learning material being studied. Technology-based learning media has an important role as an intermediary between teachers and students in delivering learning material. The development and progress of science and technology is increasingly rapid and cannot be avoided, so creative and innovative educators are needed in developing learning media and resources. The Merdeka Curriculum is a reform effort in the education system in Indonesia which emphasizes developing the competencies and character of students in a more flexible and contextual manner. Efforts to improve the quality of education in Indonesia must be accompanied by technological developments. This research uses a Library Research approach with qualitative analysis based on the theory used, namely content analysis to strengthen the study with this theme. Library Research is library research by examining sources in the form of books, manuscripts, notes, etc. The use of learning media in the learning process cannot be separated from the student learning process, because the use of learning media that suits students' needs is to help students achieve learning goals